Analysis of Students' Communication Politeness Capabilities Towards Lecturers in an Academic Environment: Case Study at FKIP Universitas Perjuangan Tasikmalaya - Jumadil Saputra; Setyo Yohandoko; Volodymyr Rusyn (International Journal of Ethno-Sciences and Education Research, 2024)
This research investigates students' polite communication skills towards lecturers in an academic environment. Data was collected through observations and interviews with students from the Indonesian Language and Literature Education Study Program at FKIP Universitas Perjuangan Tasikmalaya. The main finding is that most students tend to use less polite language in communication with lecturers, including the use of slang, non-compliance with communication ethics, and lack of use of polite words such as "thank you." Factors such as the living environment and relationships outside campus influence student communication patterns. The modern era of technology and easy access to digital content has also influenced their communication practices. This influence has the potential to damage the campus' reputation and create disharmony in the academic environment. Awareness of the importance of language politeness and the active role of educational institutions and lecturers in providing guidance on communication ethics can help create a more conducive academic environment.